Mechanisms of Property Access in 'the throat' of New Spain. Social Relationships, Customs, and Rights in Veracruz: 1680-1770 (Historia Agraria de América Latina, 2025)
The article analyzes the mechanisms that allowed families, workers and communities to gain access to lands of mayorazgos and municipal corporations. The territory adjacent to the city of Veracruz in New Spain is taken as a space of analysis, in a period that begins in the last decades of the seventeenth century and ends in the initial phase of Bourbon militarization. During that period, a hierarchical and ethnically diverse society was consolidated and its members settled in haciendas, ranches and places, where they dedicated themselves to carrying out different productive activities. The access and permanence of families in their sites is explained by the importance of piety, custom, and the notions of justice and common good as referents of a shared culture that influenced the agreements made by owners, administrators, tenants and stewards to distribute the usufruct of the land and reduce conflicts. These circumstances produced a variety of property rights that did not always need written testimony when the compromises established between the social actors were the parameter that gave them value and durability.
Keywords: property; mayorazgos; social groups; custom; reciprocity